The virtual restraining order as a novel cyber precautionary measure to combat online crime - García Sánchez, María Dolores (Rivista italiana di informatica e diritto, 2025)
In light of the increasing digitalization of criminal conduct, the necessity of proportionate and effective precautionary measures has become a critical concern in contemporary criminal justice. Accordingly, this research explores the extent to which traditional precautionary frameworks can be adapted to address the unique challenges posed by cybercrime while ensuring compliance with fundamental rights. The examination of precautionary measures within the digital sphere, with particular emphasis on what we define as cyber-precautionary measures, constitutes a fundamental aspect of contemporary criminal justice. This study adopts a progressive analytical approach, commencing with a general overview of this emerging category of precautionary measures in criminal proceedings before advancing to an in-depth analysis of a novel proposal: the virtual restraining order. The research further investigates the technical and legal feasibility of this new cyber-precautionary measure, as well as the role of Internet Service Providers in implementing it. Subsequently, the discussion will focus on the specific legal and practical dimensions of this measure, with particular attention to its implications for fundamental rights, the principle of proportionality, and its practical implementation.L’ordine di allontanamento virtuale come nuova misura cautelare cibernetica per combattere il crimine onlineAlla luce della crescente digitalizzazione delle condotte criminali, la necessità di misure cautelari proporzionate ed efficaci è diventata una questione cruciale nella giustizia penale contemporanea. Di conseguenza, questa ricerca esplora quanto le misure cautelari tradizionali possano essere adattate per affrontare le sfide uniche poste dalla criminalità informatica, garantendo al contempo il rispetto dei diritti fondamentali. L’analisi delle misure cautelari nell’ambito digitale, con particolare enfasi su quelle che definiamo misure cibernetiche, costituisce un elemento fondamentale della giustizia penale contemporanea. Questo studio adotta un approccio analitico progressivo, partendo da una panoramica generale di questa categoria emergente di misure cautelari nei procedimenti penali, per poi approfondire una proposta innovativa: l’ordine di restrizione virtuale. La ricerca esamina inoltre la fattibilità tecnica e giuridica di questa nuova misura cibernetica cautelare, nonché il ruolo dei fornitori di servizi Internet nella sua attuazione. Successivamente, la discussione si concentrerà sugli aspetti giuridici e pratici specifici di questa misura, con particolare attenzione alle sue implicazioni per i diritti fondamentali, il principio di proporzionalità e la sua applicazione pratica.